Understanding the potential release of microplastics from coatings used on commercial ships - Tamburri, Mario N.; Soon, Zhi Yang; Scianni, Christopher; Øpstad, Christer L.; Oxtoby, Neil S.; Doran, Simon; Drake, Lisa A. (Frontiers in Marine Science, 2022)
Microplastic pollution in the ocean is a critical, global environmental concern. Although believed to be a comparatively small contributor, the paints applied to commercial ships have been identified as a source of microplastics because polymers are used as binding agents in all anticorrosive and antifouling marine coatings. Furthermore, the release of microplastics from coatings may be amplified by in-water cleaning operations to remove biofouling. A comprehensive, detailed assessment and review of the array of commercial ships’ coatings, specifically characteristics, behavior, and fate over time, has not been conducted in the context of ocean microplastic pollution. This Policy Brief identifies gaps and proposes actions to better understand the fate of released particles with the goal to inform appropriate and effective solutions.